To read the political discourse - Razzeto, Mario (1986)
This text is a preliminary essay about the nature and the components of political discourse, a semiotic domain that will be the subject of a detailed analysis in an ongoing investigation, whose elaboration I share with Oscar Quezada. Here we are now trying to explore, to probe, to define the object of work and to present some general considerations.